2011
DOI: 10.1542/peds.2010-1449
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Infection Reduction in VLBW Infants With a Statewide Quality-Improvement Model

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Quality-improvement techniques are increasingly effective as they move from passive dissemination to interactive techniques between those authoring practice change packages and their audiences. However, resource constraints and the many potential topics mitigate against prescribing intense collaboratives for every topic. WHAT THIS STUDY ADDS:Efficient progress in decreasing neonatal nosocomial infection rates can be achieved when statewide quality-improvement collaboratives using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
79
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 46 publications
1
79
0
Order By: Relevance
“…For critically ill neonates, incidence rates of CLABSI decreased by 4% per quarter (61% decline during the study period), whereas incidence rates of VAP declined by 3% per quarter (50% decline during the study period), representing sustained improvement for this vulnerable population. These findings are similar to reported decreases in CLABSI for neonates in state [23][24][25][26] and multistate collaborations. 27 Similar to previous studies, 1,20 we found that very low birth weight (VLBW) infants were more likely to have CLABSI or VAP than normal birth weight infants.…”
Section: Discussionsupporting
confidence: 89%
“…For critically ill neonates, incidence rates of CLABSI decreased by 4% per quarter (61% decline during the study period), whereas incidence rates of VAP declined by 3% per quarter (50% decline during the study period), representing sustained improvement for this vulnerable population. These findings are similar to reported decreases in CLABSI for neonates in state [23][24][25][26] and multistate collaborations. 27 Similar to previous studies, 1,20 we found that very low birth weight (VLBW) infants were more likely to have CLABSI or VAP than normal birth weight infants.…”
Section: Discussionsupporting
confidence: 89%
“…Prevention of central line associated bloodstream infection (CLABSI) and other hospital-acquired infection in the NICU has been a recent target of quality improvement efforts. [5][6][7] Such efforts share the broader strategic objective of reducing health care misuse (1 of 3 categories of quality problems, along with underuse and overuse). 8 In 2012, more than 60% of NICUs in California reported a CLABSI rate of zero.…”
mentioning
confidence: 99%
“…[2][3][4][5][6] Adopting evidence-based changes has been enhanced by participation in collaborative quality improvement (QI) projects, where changes are bundled together and implemented by teams from different centers sharing common strategies. 7,8 Collaborative QI, based on the Institute for Healthcare Improvement' s (IHI) model, 9 has been successful in settings such as the California Perinatal Quality Care Collaborative (CPQCC). 6,[7][8][9][10] This model brings together teams from different institutions, providing structured learning with face-to-face meetings, Web-based discussions, electronic mailing lists, expert panel access, and unblinded outcome and process data display, with incremental learning through reporting of successes, barriers, and lessons learned.…”
mentioning
confidence: 99%